2011
DOI: 10.1148/radiol.11102350
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Early Dynamic Blood Flow and Late Standardized Uptake Value Determination in Hepatocellular Carcinoma

Abstract: Early dynamic blood flow FDG PET/CT may be used to help discriminate and characterize HCC tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 16 publications
2
38
1
Order By: Relevance
“…Compared with other ED 18 F-FDG PET or CE CT studies (19,21,22), we found a relatively late peak signal in timeactivity curves for both tumor and nontumor tissue. This observation is explained by the fact that we did not adjust our measurements by g-variate fitting-that is, we did not use a mathematic function to exclude recirculation (19,23).…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Compared with other ED 18 F-FDG PET or CE CT studies (19,21,22), we found a relatively late peak signal in timeactivity curves for both tumor and nontumor tissue. This observation is explained by the fact that we did not adjust our measurements by g-variate fitting-that is, we did not use a mathematic function to exclude recirculation (19,23).…”
Section: Discussioncontrasting
confidence: 55%
“…The present protocol therefore simplified that of Bernstine et al (19) in 2 main ways. First, using ED 18 F-FDG PET/CT to generate CE CT-like images-that is, to depict the arterial, portal venous, and venous phases-and relying largely on simple visual and descriptive endpoints, we reconstructed fewer frames with longer times: 4 frames at 15-s intervals, then 3 frames at 60-s intervals, versus 18 frames at 5-s intervals.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations